Prognostic factors of calcaneal osteomyelitis. (August 2014) - Merlet, Audrey; Cazanave, Charles; Dauchy, Frederic-Antoine; Dutronc, Hervé; Casoli, Vincent; Chauveaux, Dominique; De Barbeyrac, Bertille; Dupon, Michel
Abstract Background: Calcaneal osteomyelitis is difficult to manage and requires a multidisciplinary approach. The aim of this study was to describe the characteristics and outcomes of calcaneal osteomyelitis, and to determine prognostic factors. Methods: This was an observational and retrospective study including all patients presenting with calcaneal osteomyelitis referred to a tertiary referral centre between January 2005 and December 2010. Results: Forty-two patients (mean age 50.7 y, range 22–89 y) were included. Fifteen were female. The mean duration of follow-up was 20 months (range 12–48 months). Twenty-six (62%) were post-traumatic osteomyelitis and 16 (38%) were secondary to neurological damage (sensitivity or motor impairment). All patients underwent surgical management with bone curettage and appropriate antibiotic therapy. Staphylococcus aureus was the most commonly isolated bacterium and was found in 29 patients. Polymicrobial samples were observed in 29 patients. Pseudomonas aeruginosa was associated with calcaneal osteomyelitis secondary to neurological damage (n = 7; 44% p = 0.045). Twenty-eight patients (66.7%) healed without the need to resort to amputation. The mean time to healing was 29 weeks with a range of 4–144 weeks. Relapse of bone infection occurred in 17 patients (40.5%). Seven patients (16.7%) required amputations. Favourable prognostic factors for healing without amputation were an American Society of Anesthesiologists (ASA) score < 2 (p < 10−4), post-traumatic calcaneal osteomyelitis (p = 0.001), age < 65 y (p = 0.02), absence of neuropathy (p = 0.005), and absence of diabetes mellitus (p = 0.02). Conclusions: Calcaneal osteomyelitis is characterized by frequent relapse with delayed wound healing. Clinicians should take into account the impact of older age, as well as co-morbidities such as diabetes mellitus or the presence of neuropathy, during the routine management of patients with this difficult-to-treat bone infection.